DISIPLIN WARGA BELAJAR DALAM MENGIKUTI KEGIATAN BELAJAR MENGAJAR PROGRAM KESETARAAN DI PKBM KAK SETO PEKANBARU KECAMATAN SAIL KOTA PEKANBARU - Puput Diana; Aswandi Bahar; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is based on high discipline of studying citizens in participating in teaching and learning of equivalency program in PKBM Kak Seto Pekanbaru Sail Sub-district Pekanbaru City. The formulation of this research problem is how high the level of Discipline Students Learn In Following Teaching and Learning Activities Equalization Program in PKBM Kak Seto Pekanbaru Sail Sub-District Pekanbaru ?. The purpose of this study is to determine the level of discipline learners in participating in teaching and learning activities equivalency program in PKBM Kak Seto Pekanbaru Sail Sub-District Pekanbaru. The population in this study as many as 36 citizens of study and sample of this study 33 people studying with a critical level of 5%, the sample used is proporsionate stratified random sampling. The instrument of data collection is questionnaire with 70 statement and after trial live 61 valid statement to be made in research instrument. Data analysis through Quantitative Descriptive analysis. From the calculation of the presentation of the answers obtained the findings of research discipline study participants in participating in teaching and learning activities equivalence program in PKBM Kak Seto Pekanbaru Sail District Pekanbaru City is the percentage of 56.92%. This means being moderate.Keywords: Discipline, Learning Community, Teaching and Learning Activities,Equality Program, PKBM